PERATURAN DAERAH, ANTARA KEPENTINGAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH - Supriyadi Supriyadi (Jurnal Cakrawala Hukum, 2016)
Regional Regulation as one of law regulation product is an instrument for regulating government matters that include in regional autonomy matters. Especially for Municipal or City Law Regulation, regulating authority is held on Municipal or City House of Representatives and its leader. Normatively, the existence of Municipal or City Regulation is formed to regulate about the providence government business that includes in regional autonomy, despite from expose the higher law regulation and regulate the unique character of the region that depends on law and norms. The enforcement of the legal regulation is expected to be mean to perceive national policy and government development program in order to reach national goal. Practically, it is not close chances that the legal regulation from regional formed is not relevant to the natiional goal. When that happened, Ministry of Domestic Affair and Governor can directly cancel the irrelevant law regulation unless Constitutional Court cancels that authority, the Central government no longer has authority to cancel it. It has to be done by an assessment through Judicial Review under Supreme Court. This condition could be an obstacle in development accelerate, especially in economic sector in term of creating business and investment in the regional area.